Wykorzystanie performatywnej funkcji języka w dyskursie publicznym na przykładzie sporu o legalizację związków partnerskich - Bartoszewicz, Joanna (Warszawskie Studia Teologiczne, 2017)
Language has a creative role, which establishes new language quality and through its performative function it influences the creation of reality, relations and public mood and, as a consequence, also legislative processes. In this article I assume that language does not solely play the role of an information transmitter. Thanks to its performative function it also influences human behaviour. In the article, on the basis of discourse analysis concerning the registered partnerships legalisation, I will outline the issue of discourse participants’ language behaviours as well as the means of commenting on a given event. I will also present language features characteristic for a given group participating in a communication process.